2022
DOI: 10.1001/jamaneurol.2022.2184
|View full text |Cite
|
Sign up to set email alerts
|

Levodopa Content of Mucuna pruriens Supplements in the NIH Dietary Supplement Label Database

Abstract: This case series assesses the levels of levodopa in Mucuna pruriens supplements available in the US that are included in the National Institutes of Health Dietary Supplement Label Database.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…In most of these experimentations, however, there is no characterization of the extracts. There is just L-dopa quantification, although their content does not always correspond with the declared on the label [38]. In this work, we decided to investigate the component resultants on the Mucuna seed extract to be more precise on the potential effects it could result in experimentations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In most of these experimentations, however, there is no characterization of the extracts. There is just L-dopa quantification, although their content does not always correspond with the declared on the label [38]. In this work, we decided to investigate the component resultants on the Mucuna seed extract to be more precise on the potential effects it could result in experimentations.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are few characterizations of the molecules in these extracts beyond L-dopa, and their direct use in animal experiments is customarily done [36]. Notably, there are many commercial suppliers of both seeds in powder and seed extracts with a wide range of levodopa content [37] [38]. But these are poorly characterized, or no metabolite composition is reported in these products.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have reported mislabeling of both generic drugs and dietary supplements. 1,2 While the regulatory framework for prescription drugs and dietary supplements are distinct in the US, labels in both categories are required to accurately represent the products' contents. To our knowledge, whether label accuracy differs between generic drugs and dietary supplements containing the same active pharmaceutical ingredient has not been studied.…”
mentioning
confidence: 99%
“…Alternative practitioners have proposedMucuna pruriens as a treatment for parkinsonism which may be more palatable to some patients, despite containing the same primary active ingredient 4 . The levodopa content of Mucuna pruriens extracts is quite variable, and measured amounts can range from nearly negligible to more than twice the stated amount 5 .DRT is associated with side effects including dyskinesias, impulse control disorders, and psychosis. The pathophysiology of impulse control disorders is complex but linked to changes in striatal dopamine signaling induced by exposure to pulsatile dopamine.…”
mentioning
confidence: 99%